LANGUAGE AS A REFLECTION OF THINKING - Abdurrahman Hi Usman; Adi F Mahmud; Abdulhalim Daud; Suratman Dahlan (EDUKASI, 2021)
The study deals with humans’ language performance connected to mind, thought, intelligence and way of thinking. The discussion was elaborated through ideas and argumensts explored in the work of library research design. The data were collected and presented in descriptive-qualitative way. The data were obtained from many sources concerning with the topic. Based on the research results, it was found that someone’s language performance is also identified as the ability, quality, and activity of thinking. Someone can be known, recognized, and respected by other people through his/her intelligence and way of thinking. It is caused by the function and urgency of language in human’s everyday life. In the process of thinking, someone requires language/languages to identify, characterise, communicate, and explain what he/she is thinking. It means that someone’s ability of performing or communicating ideas in a language reflects his/her quality of thinking and intelligence. The better someone in thinking and producing ideas the higher quality of communication in language he/she performs. The degree of someone’s intelligence and way of thinking can be measured through the quality of his/her communication in language. The fluency and accuracy of someone’s language production is the reflection of his/her ability of mind and thoughts.